2022
DOI: 10.3389/fphar.2022.1022294
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of antitumor drug targets prediction using integrated bioinformatic analysis for immunogenic cell death-related lncRNA model based on stomach adenocarcinoma characteristics and tumor immune microenvironment

Abstract: Stomach adenocarcinoma (STAD) ranks as the fourth prevalent cause of mortality worldwide due to cancer. The prognosis for those suffering from STAD was bleak. Immunogenic cell death (ICD), a form of induced cellular death that causes an adaptive immune response and has increasing in anticancer treatment. However, it has not been ascertained how ICD-related lncRNAs affect STAD. Using univariate Cox regression and the TCGA database, lncRNAs with prognostic value were identified. Thereafter, we created a prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Gastric cancer cells can Frontiers in Pharmacology frontiersin.org avoid monitoring and attack by the immune system (Schreiber et al, 2011). Immune evasion is closely associated with the immune microenvironment, which could become a new aspect of research on gastric cancer treatment (Wang et al, 2021b;Ding et al, 2022;Gao et al, 2022;Han et al, 2022;Liao et al, 2022;Xu et al, 2022). Therefore, we analyzed the effect of ICD-related gene mutations on immune cell Frontiers in Pharmacology frontiersin.org 10 infiltration in the high-and low-risk groups and found that there were statistically significant differences between the two groups in many immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric cancer cells can Frontiers in Pharmacology frontiersin.org avoid monitoring and attack by the immune system (Schreiber et al, 2011). Immune evasion is closely associated with the immune microenvironment, which could become a new aspect of research on gastric cancer treatment (Wang et al, 2021b;Ding et al, 2022;Gao et al, 2022;Han et al, 2022;Liao et al, 2022;Xu et al, 2022). Therefore, we analyzed the effect of ICD-related gene mutations on immune cell Frontiers in Pharmacology frontiersin.org 10 infiltration in the high-and low-risk groups and found that there were statistically significant differences between the two groups in many immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al screened five lncRNAs based on 34 ICD-related genes to construct a prognostic model for gastric adenocarcinoma. The model could predict the cumulative survival rate and guide individual treatment ( Ding et al, 2022 ). The aforementioned studies all indicated that ICD was closely related to lncRNAs and to disease prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of apparent symptoms in the early stages of GC, many patients are diagnosed at advanced stage 5 , 6 . STAD is the most common and malignant subtype 7 . Surgery remains the cornerstone of GC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenic cell death (ICD), which enhances tumor activation by the immune system of an immunoactive host, is a speci c variant of regulatory cell death [7]. It is driven by stress and can induce adaptive immunity against dead cell antigens, similar to the host immune system's second strike against tumor cells [8].…”
Section: Introductionmentioning
confidence: 99%